TRADITIONAL HOUSE AS PUBLIC SPACE IN INDIGENOUS NEIGHBORHOOD SETTLEMENT OF SAHU REGION, WEST HALMAHERA - Sherly Asriany; Muhammad Tayeb; Ridwan Ridwan (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Lack of public space as a place of social interaction is one of the problems in the settlement neighborhood, especially in Indigenous neighborhoods settlement of Sahu region, West Halmahera. Sahu Village is one of the villages locates in West Halmahera regency, North Maluku Province. This study aims to identify the functions of traditional Sahu house as public space that is used by residents of the area for social interaction. The method used was naturalistic and qualitative research behavior by observing the activities of people who use public space spread over several indigenous areas in Sahu region. The results showed that: 1) The traditional house is a public space that is used by family members, neighbors and others who visit the region, 2) The traditional house is used as a multi-function space solving the problem of indigenous and customary meal, as well as other social activities, 3) Traditional house located in an area that is easily seen and visited in order to be used by everyone.